Evaluation du niveau de connaissance du lexique BIRADS-ACR par les radiologues exerçant en Afrique francophone sub-saharienne - AKANNI Djivèdé Witchékpo Maurice Mohamed; DAMIEN Barikissou Georgia; ADJADOHOUN Sonia; KIKI Miralda; YEKPE-AHOUANSOU Patricia; SAVI de TOVE Kofi-Mensa; N’ZI Kouassi Paul; BIAOU Olivier; BOCO Vicentia (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2023)
Objectives: The study aimed to assess the level of knowledge of the 5th version of the BIRADS-ACR lexicon among sub-Saharan French-speaking African radiologists. Materials and Methods: a descriptive and analytical cross-sectional study in the form of a questionnaire was carried out by a direct survey of radiologists and residents during the French-speaking African radiology meeting held in Cotonou, Benin, from 22 to 24 May 2019. Knowledge was assessed on the standardized vocabulary of the BIRADS-ACR lexicon, the four semiologic entities in mammography, and on writing a structured mammography report. The Global Knowledge Score (GKS) was calculated from correct answers to the questions (n =20) and classified as "Good", "Average" or "Poor". The link between participants’ professional experience and GKS was analyzed. Results: A total of 74 participants were included. The mean GKS of the study population was 6.42 ± 3.92 with extreme values between 0 and 20. The GKS was classified as "Poor," "Average," and "Good" in 91.89%, 2.70%, and 5.41% of the study population, respectively. The mean GKS of radiologists with less than five years of professional experience was 1.89 times higher than that of residents (p = 0.021). A good overall knowledge of the standardized vocabulary of the 5th version of the BIRAD-ACR lexicon was found in 8.11% of the study population. Good knowledge of the four semiologic entities in mammography was respectively 37.83% for mass, 19.18% for density asymmetry, 20.27% for architectural distortion, and 31.08% for calcification. Only 6.76% of the radiologists had a good knowledge of the mandatory items to be included in a structured mammography report. Conclusion: The level of knowledge of the 5th version of the BIRADS-ACR lexicon among French-speaking African radiologists was globally poor. RESUME Objectifs : évaluer le niveau de connaissance de la 5ème version du lexique BIRADS-ACR chez les radiologues africains francophones subsahariens. Matériels et Méthodes : une étude transversale descriptive et analytique sous forme de questionnaire a été réalisée par une enquête directe auprès des médecins radiologues et des DES-RIM lors des journées de Radiologie d’Afrique Noire Francophone tenues à Cotonou au Bénin du 22 au 24 mai 2019. Les connaissances ont été évaluées sur le vocabulaire normalisé du lexique BIRADS-ACR, les quatre entités sémiologiques en mammographie, et sur la rédaction d’un compte rendu structuré en mammographie. Le Score Global de Connaissance (SGC) a été calculé à partir de bonnes réponses aux questions (n =20) et classé en « Bon », « Moyen » ou « Mauvais ». La relation entre l’expérience professionnelle et le SGC des participants a été analysée. Résultats : Au total, 74 participants étaient inclus. La moyenne du SGC de la population d’étude était de 6,42 ± 3,92 avec des valeurs extrêmes entre 0 et 20. Le SGC était classé « Mauvais », « Moyen » et « Bon » chez respectivement 91,89%, 2,70% et 5,41% de la population d’étude. La moyenne du SGC des médecins radiologues ayant moins de cinq année d’expérience professionnelle était 1,89 fois plus élevée que celui des DES-RIM (p = 0,021). Une bonne connaissance globale du vocabulaire normalisé de la 5ème version du lexique était retrouvée chez 8,11% de la population d’étude. La bonne connaissance des quatre entités sémiologiques en mammographie était respectivement de 37,83% pour la masse, 19,18% pour l’asymétrie de densité, 20,27% pour la distorsion architecturale, et de 31,08% pour la calcification. Seulement 6,76% des radiologues avaient une bonne connaissance des items obligatoires à renseigner dans un compte rendu structuré de mammographie. Conclusion : Le niveau de connaissance de la 5ème version du lexique BIRADS-ACR chez les radiologues africains francophones était globalement faible.